2016
DOI: 10.1038/srep32731
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific Co-expression of Long Non-coding and Coding RNAs Associated with Breast Cancer

Abstract: Inference of the biological roles of lncRNAs in breast cancer development remains a challenge. Here, we analyzed RNA-seq data in tumor and normal breast tissue samples from 18 breast cancer patients and 18 healthy controls and constructed a functional lncRNA-mRNA co-expression network. We revealed two distinctive co-expression patterns associated with breast cancer, reflecting different underlying regulatory mechanisms: (1) 516 pairs of lncRNA-mRNAs have differential co-expression pattern, in which the correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 57 publications
4
22
0
1
Order By: Relevance
“…While most of these pairs (2698, 91.2%) were on the different chromosome ( trans -acting), suggesting that most of the regulation of lncRNA and mRNA expression was in a trans way. These findings are also consistent with previous reports [ 23 , 24 ].…”
Section: Resultssupporting
confidence: 94%
“…While most of these pairs (2698, 91.2%) were on the different chromosome ( trans -acting), suggesting that most of the regulation of lncRNA and mRNA expression was in a trans way. These findings are also consistent with previous reports [ 23 , 24 ].…”
Section: Resultssupporting
confidence: 94%
“…This suggested that most of the lncRNA trans-regulate mRNA expression. Such regulation pattern was also observed in a human cancer-related study (Wu et al, 2016).…”
Section: Coexpression Of Lncrna and Mrna In Bovine Mammary Gland Tissuesupporting
confidence: 74%
“…Functional studies in humans have used similar models. Wu et al (2016) used this method to identify lncRNA-mRNA coexpression pairs associated with breast cancer, and Guo et al (2015) investigated the expression patterns of lncRNA and mRNA in ovarian cancer malignant progression. Thus, using this model might help improve lncRNA annotation.…”
Section: Xloc_306924mentioning
confidence: 99%
“…Li et al (2018a) found that some of the correlations between microRNA and target genes declined in cancer compared to normal across multiple cancers. Wu et al (2016a) found two kinds of lncRNA-mRNA co-expression patterns: 1) correlations between lncRNA-mRNA in cancer were reversed compared to normal; 2) correlations between lncRNA-mRNA in cancer were similar to normal. Xiao et al (2018) compared the differential genes between ER+ and ERand constructed a ceRNA network and found that some molecules correlated with prognosis.…”
Section: Discussionmentioning
confidence: 96%